Crystallization And Catalytic Behavior Of Organo-Template Free K-F Zeolite Nanocrystals In Aldol Condensation Of Benzaldehyde And Heptanal - Wong, Siew Fang (2017)
The aim of this project was to study the crystal growth of K-F zeolite nanocrystals (structure code EDI) synthesized from organo-template-free precursor mixture. K-F zeolite nanocrystals were synthesized under hydrothermal condition. Fully crystalline nanosized K-F zeolite crystals with flattened cuboid shape morphology were obtained within 3.0 h at 100 °C. These nanocrystals tended to agglomerate to form secondary spherical particles. K-F zeolite nanocrystals were also synthesized under microwave irradiation at 100 °C where rice husk ash (RHA) was used as an alternative silica source.